Manufacturing method for α+β titanium alloy ingot and rod
By refining the casting structure of α+β-type titanium alloy rods through controlled electronic beam or plasma dissolution, the method addresses surface flaws and chemical inconsistencies, achieving cost-effective and high-quality rods for 3D printing applications.
Patent Information
- Application Number
- JP2023503569
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-02
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2041-03-02
AI Technical Summary
Existing methods for manufacturing α+β-type titanium alloy rods face issues such as oversized crystal grains leading to cracks and voids, which degrade the surface quality and increase production costs due to deep flaws and variations in chemical composition, particularly when omitting traditional forging processes.
The method involves directly rolling α+β-type titanium alloy cast mass without forging, using controlled electronic beam or plasma dissolution to refine the casting structure, with specific chemical compositions and dimensions to minimize surface flaws and ensure uniformity.
This approach results in a stable, cost-effective production of titanium alloy rods with improved surface properties, suitable for use in 3D printing, by reducing surface flaws and maintaining consistent chemical composition.
Smart Images

Figure 0007623611000007 
Figure 0007623611000008 
Figure 0007623611000009
Abstract
Description
[Technical field]
[0001] The present invention relates to α +β-type titanium alloy ingot and a method for manufacturing the rod Regarding. [Background technology]
[0002] The manufacturing process for α+β titanium alloy bars generally consists of a process of producing titanium alloy ingots by melting and casting titanium sponge, mother alloy, titanium scrap, etc. as molten raw materials, a blooming process in which the titanium alloy ingots are heated to the β region and forged or rolled, and a rolling process in which the ingots are heated to the β region or α+β region and made into bars. On the other hand, in order to reduce costs, it is possible to omit the blooming process and directly roll the titanium alloy ingots to produce bars.
[0003] For example, Patent Document 1 discloses a method for producing a titanium lump, which includes a compression molding step of obtaining a titanium briquette by compression molding one or more selected from titanium sponge and titanium scrap and an auxiliary material containing an element required for adjusting the chemical composition, and a melting step of irradiating the surface of the titanium briquette with an electron beam under a reduced pressure of 1 Pa or less to melt all of the titanium briquette to obtain a titanium lump. In the method for producing a titanium lump described in Patent Document 1, the melting step includes a step of irradiating an arbitrary surface of the titanium briquette with an electron beam to melt a part in the thickness direction from the surface, and a step of irradiating an arbitrary other surface with an electron beam to melt at least the unmelted titanium briquette. In the method for producing a titanium lump described in Patent Document 1, a titanium lump having a plate shape with a thickness of 7 to 80 mm, a cylindrical shape in which a cross section perpendicular to the longitudinal direction is a circle with a diameter of 10 to 80 mm, or a columnar shape in which a polygon with a pentagon or more sides with a circle equivalent diameter of 10 to 80 mm is produced.
[0004] In addition, titanium alloy powder produced from titanium alloy rods is used as material for manufacturing objects using 3D printers.
[0005] Patent Document 2 describes a technology for using metal powder as a material and a 3D printer to create objects. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2019 / 26251 [Patent Document 2] Japanese Patent Application Publication No. 2017-222899 Summary of the Invention [Problem to be solved by the invention]
[0007] However, Patent Document 1 discloses a preferred manufacturing method for thin titanium ingots with a thickness of 80 mm or less, and the technology described in Patent Document 1 is a technology in which the surface of a titanium briquette is irradiated with an electron beam to melt the titanium briquette, and then the molten titanium briquette is solidified to manufacture a titanium ingot. In order to manufacture a large titanium ingot by irradiating the surface of the titanium briquette with an electron beam, it is necessary to increase the melting depth of the titanium briquette by the electron beam. However, if the melting depth of the titanium briquette by the electron beam is increased, the cooling rate after melting is reduced, and the crystal grains become coarse. If the crystal grains are coarse, cracks and voids may occur when the titanium alloy ingot is rolled into a bar, and deep scratches may be formed on the surface of the bar. Thus, there is room for improvement in the technology described in Patent Document 1.
[0008] When the blooming process is omitted and the ingot is directly hot-rolled to produce the bar, there is a problem that the surface quality of the bar deteriorates due to the coarse cast structure, resulting in a decrease in yield. In particular, in an α+β titanium alloy containing Al and O as α stabilizing elements and Fe as β stabilizing element, the diffusion rate of Fe is fast and the solid solubility limit of Fe in the α phase is small, so that a film-like α phase may precipitate at the β grain boundary during the transformation from the β phase to the α+β phase. The film-like α phase precipitated at the β grain boundary may become the starting point of cracks in the α+β titanium alloy bar, resulting in a decrease in yield. Therefore, in order to omit the blooming process, it is necessary to produce an ingot that reduces the depth of surface defects in the bar obtained by rolling the titanium alloy ingot. In the following, the film-like α phase precipitated at the β grain boundary may be referred to as the grain boundary α phase.
[0009] In addition, if the titanium alloy bar has deep flaws, the yield rate will decrease to remove the flaws, which will increase the manufacturing cost, and the chemical composition of the titanium alloy powder produced from the titanium alloy bar with the flaws may vary. The raw material for titanium alloy powder for 3D printers is, for example, produced by melting titanium alloy bar and using a gas atomization method, but if the titanium alloy bar has a large flaw, oxide scale or foreign matter may adhere to the flawed part. If oxide scale or foreign matter adheres to the flawed part, the titanium alloy powder produced by melting the flawed part will have a different chemical composition from the titanium alloy powder produced from the flawless part. In the part molded with titanium alloy powder of different chemical composition using a 3D printer, problems such as a change in strength compared to other parts may occur. Therefore, it is preferable that the titanium alloy powder for 3D printers has a uniform chemical composition. Therefore, it is preferable that the titanium alloy bar used as the raw material for titanium alloy powder for 3D printers has fewer large flaws.
[0010] Furthermore, there have been no known cases in which surface defects in titanium alloy rods having a diameter of 80 mm or more have been suppressed when titanium alloy rods are produced by directly hot rolling them without blooming the titanium alloy ingots.
[0011] In view of the above circumstances, the present invention aims to provide an ingot of an α+β type titanium alloy containing Al, Fe, and O, which can be used to industrially produce rods with good surface properties (with shallow surface defects) at low cost and in a stable manner, even when the rods are produced by directly hot rolling without blooming forging. [Means for solving the problem]
[0012] The present inventors have intensively studied a method for producing a bar with good surface properties by directly hot rolling an α+β type titanium alloy ingot without blooming forging the α+β type titanium alloy ingot by improving the properties of the ingot.
[0013] In order to improve the surface properties of the bar material, it is first considered to refine the cast structure of the α+β type titanium alloy ingot. In order to refine the cast structure of the α+β type titanium alloy ingot, it is more preferable to manufacture it using the electron beam melting method (EBM) or plasma melting method (PAM) than the consumable electrode vacuum arc melting method (VAR), because there is more freedom in the mold shape and the solidification speed can be increased.
[0014] The crystal grain size of an α+β titanium alloy ingot produced by electron beam melting or plasma melting (hereinafter, the crystal grain size may be simply referred to as grain size) is affected by the size of the α+β titanium alloy ingot. The grain size of the cast structure in an α+β titanium alloy ingot with a diameter of 200 mm is generally about 10 to 20 mm. As a result of research, the inventors have found that in direct hot rolling without blooming forging, in order to suppress surface defects of the bar material, it is effective to refine the grain size of the α+β titanium alloy ingot to 10 mm or less and 1 / 100 or less of the circumference of the α+β titanium alloy ingot.
[0015] However, the above-mentioned measures alone are not sufficient to reduce the depth of surface defects on the bar material to a certain standard or less.
[0016] As a result of the study by the inventors, when a titanium alloy ingot is heated to the β region and rolled to a reduction of area of 74%, and the cross section is observed, it is found that recrystallized β crystal grains with a grain size of about 5 mm are formed on the surface layer, and further, a film-like α phase is formed on the grain boundaries of the recrystallized β crystal grains. Furthermore, it is found that cracks occur along the film-like α phase formed on the grain boundaries of the recrystallized β crystal grains, and the cracks are connected to the surface. And, it is found that the cracks caused by the film-like α phase formed on the grain boundaries of the recrystallized β crystal grains reach deep positions, and become deep flaws in the bar material, which is a factor that significantly reduces the yield.
[0017] As a result of further investigation, the inventors have found that controlling the contents of Al, Fe, and O within certain ranges is effective in controlling the formation of the grain boundary α phase in a titanium alloy ingot and reducing the surface defect depth of the bar material.
[0018] The present invention was made through further investigation based on the above findings, and the gist of the present invention is as follows.
[0019] (1) According to one aspect of the present invention 、α A +β type titanium alloy ingot, containing, by mass%, Al: 2.5-8.0%, Fe: 0.5-3.0%, Sn: 0-3.0%, Zr: 0-3.0%, Mo: 0-3.0%, Si: 0-3.00%, Cu: 0-3.0%, Nb: 0-3.0%, and an amount of O that satisfies the following formula (1), with the balance being Ti and impurities, has a chemical composition, and the area S (mm 2 The ratio L / S of the perimeter L (mm) of the cross section to the total length of the α+β type titanium alloy ingot is 0.010 or more, and from one of the two end faces in the longitudinal direction of the α+β type titanium alloy ingot to the other end face, the portion of 20 to 80% of the total length of the α+β type titanium alloy ingot in the longitudinal direction The cross section of In the above, the surface of the α+β type titanium alloy ingot is Inside At a position 10 mm toward Calculated on a line corresponding to the shape of the cross sectionThe grain size D of the cast structure satisfies D≦10 mm and D≦L / 100, and the thickness of the α+β type titanium alloy ingot is 80 mm or more. Ru alpha A +β type titanium alloy ingot is provided. 0.02%≦[O]≦([Al]-[Fe]-0.5×[Mo]-0.5×[Nb]+1.0) / 100 …(1) Here, [X] indicates the content of element X in units of mass %.
[0020] (2) As described in (1) above Alpha +β-type titanium alloy ingots are made by replacing a part of the Ti with at least one of Sn, Zr, Mo, Cu, and Nb at 3.0% or more each. Lower content It may have. Effect of the Invention
[0021] According to the above-mentioned aspect of the present invention, even if an ingot of an α+β type titanium alloy containing Al, Fe and O is directly hot-rolled without blooming forging, a bar having good surface properties can be industrially produced at low cost and stably. [Brief description of the drawings]
[0022] [Figure 1] FIG. 2 is a diagram for explaining a method for measuring the average crystal grain size D of an α+β type titanium alloy ingot for hot working according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram for explaining a method for controlling the irradiation ratio of an electron beam or plasma, and is a diagram showing a schematic view of the molten metal inside a mold as viewed from the irradiation direction of an electron beam or plasma. [Diagram 3] FIG. 2 is a diagram for explaining a method for controlling the irradiation ratio of an electron beam or plasma, and is a diagram showing a schematic view of the molten metal inside a mold as viewed from the irradiation direction of an electron beam or plasma. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, the α+β type titanium alloy ingot for hot working according to one embodiment of the present invention will be described in detail. The α+β type titanium alloy is a titanium alloy whose main phases are the α phase and the β phase at room temperature (25°C).
[0024] First, the chemical composition of the hot working α+β titanium alloy ingot according to this embodiment will be described. Hereinafter, "%" means "mass%".
[0025] [Al: 2.5-8.0%] Al is an α-stabilizing element, and is contained to increase the fraction of the α phase. In the α+β-type titanium alloy ingot for hot working according to this embodiment, if the Al content is too low, the surface oxidation during heating is likely to proceed, and the thickness of the scale and the oxidized hardened layer increases, resulting in deterioration of the surface properties when the bar is made. Therefore, the Al content is set to 2.5% or more. If the Al content is too high, the ductility and toughness decrease, resulting in deterioration of the surface properties when the bar is made, so the Al content is set to 8.0% or less. The Al content is preferably 2.6% or more, more preferably 2.7% or more, and even more preferably 3.5% or more. The Al content is preferably 7.5% or less, more preferably 7.0% or less, and even more preferably 6.5% or less.
[0026] [Fe: 0.5-3.0%] Fe is an element that stabilizes the β phase, and when Fe is contained in a titanium alloy ingot, the strength is improved. Furthermore, if the content of Fe is less than 0.5%, the grain growth suppression effect of the β phase decreases, and the crystal grains tend to become coarse, so that the scratches become deep, and as a result, the surface properties of the rod material deteriorate when it is made into a rod material. Therefore, the content of Fe is set to 0.5% or more. On the other hand, if the content of Fe exceeds 3.0%, the ductility and toughness decrease, and as a result, the surface properties of the rod material deteriorate when it is made into a rod material, so the content of Fe is set to 3.0% or less. The content of Fe is preferably 0.6% or more, and more preferably 0.7% or more. The content of Fe is preferably 2.9% or less, more preferably 2.8% or less, and even more preferably 2.5% or less.
[0027] [Sn:0~3.0%, Zr:0~3.0%, Mo:0~3.0%, Si:0~3.00%, Cu:0~3.0%, and Nb:0~3.0%] The titanium alloy ingot of the present invention may contain one or more of Sn, Zr, Mo, Cu, and Nb in the range of 3.0% or less each in place of a portion of the Ti, and may contain Si in the range of 3.00% or less.
[0028] Sn, Zr, Si, and Cu are elements effective for solid solution strengthening of α-phase and β-phase, and the strength can be improved by containing them in the titanium alloy ingot. Therefore, Sn, Zr, and Cu may each be contained in an amount of 3.0% or less, and Si may be contained in an amount of 3.00% or less. The Sn content may be 2.5% or less, 1.5% or less, or 0.5% or less. The Cu content may be 2.0% or less, or 1.5% or less. The Zr content may be 2.8% or less, or 2.5% or less. Since Sn, Zr, Si, and Cu may not be contained, the Sn content, Zr content, Si content, and Cu content may each be 0% or more. The Si content may be 1.50% or less, or 0.50% or less.
[0029] Mo and Nb are β-stabilizing elements, and improve strength by solid solution strengthening, as well as ductility and hot workability. Therefore, the titanium alloy ingot may contain Mo or Nb in an amount of 3.0% or less. The Mo content may be 2.9% or less, or 2.8% or less. The Nb content may be 2.5% or less, or 2.0% or less. Since Mo and Nb may not be contained, the Mo content and the Nb content may each be 0% or more. The Mo content may be 0.5% or more. The Nb content may be 1.0% or more.
[0030] [O:0.02~0.08%] O is an α-stabilizing element, and has the effect of increasing the fraction of the α phase and improving strength. In addition, if the O content is less than 0.02%, the refining cost will increase significantly, and the effect of reducing costs cannot be obtained. Therefore, the O content is 0.02% or more. The O content may be 0.03% or more, or 0.04% or more. On the other hand, if the O content is excessive, the grain boundary α phase will be easily generated. In addition, when the hot-worked α+β-type titanium alloy ingot according to this embodiment is used as a starting material for powder used as metal powder for 3D printers, in order to ensure the strength of the molded object molded by the 3D printer, the O content of the hot-worked α+β-type titanium alloy ingot according to this embodiment is a slightly lower content than the O content required for improving strength. When a titanium alloy bar manufactured using a titanium alloy ingot as a starting material is made into a material powder used in a 3D printer, the ratio of surface area to volume increases, so that the effect of the surface oxide film becomes greater and the O content becomes higher. The O content of this titanium alloy powder is the O content of the shaped object produced by the 3D printer. The strength of the shaped object produced by the 3D printer corresponds to the O content of the shaped object. Therefore, the O content of the α+β type titanium alloy ingot for hot working according to this embodiment is slightly lower than the O content required to improve the strength. Therefore, the O content is 0.08% or less. The O content may be 0.07% or less.
[0031] [0.02%≦[O]≦([Al]-[Fe]-0.5×[Mo]-0.5×[Nb]+1.0) / 100] However, in an α+β titanium alloy containing Al and O as α stabilizing elements and Fe as β stabilizing element, the diffusion rate of Fe is fast and the solid solubility limit of Fe in the α phase is small, so that the grain boundary α phase precipitates at the β grain boundary during the transformation from the β phase to the α+β region, and becomes the starting point of cracking. O also promotes the formation of the grain boundary α phase and becomes the starting point of cracking. Mo and Nb are elements that promote the precipitation of the grain boundary α phase like Fe. Therefore, in the α+β titanium alloy ingot for hot working according to this embodiment, the O content is controlled from the viewpoint of suppressing surface defects. As a result of the study by the present inventors, it was found that there is a range of O content in which surface defects are suppressed according to the Al content, Fe content, Mo content, and Nb content. Using the content [Al] of Al, the content [Mo] of Mo, the content [Nb] of Nb, and the content [Fe] of Fe, which is a β-stabilizing element, in units of mass%, the O content [O] satisfies 0.02%≦[O]≦([Al]-[Fe]-0.5×[Mo]-0.5×[Nb]+1.0) / 100, surface defects in the bar can be suppressed. Therefore, in the α+β titanium alloy ingot for hot working according to this embodiment, the Fe content, the Al content, the Mo content, the Nb content, and the O content must further satisfy the following formula (1). 0.02%≦[O]≦([Al]-[Fe]-0.5×[Mo]-0.5×[Nb]+1.0) / 100 …(1) Here, [X] indicates the content (mass%) of element X. When the Mo content is 0, 0 is substituted for [Mo], and when the Nb content is 0, 0 is substituted for [Nb].
[0032] The balance of the chemical components is Ti and impurities. The impurities are specifically V, C, N, Y, Cr, Ni, Mn, B, H, etc. As long as they do not impair the effects of the present application, they are acceptable, and the content of impurities is less than 0.2 mass% for each element, and the total amount is 0.5% or less, which is not a problem. There is a concern that B will become coarse precipitates in the ingot. Therefore, even if it is contained as an impurity, it is preferable to suppress the B content as much as possible. In the titanium alloy plate of this embodiment, the B content is preferably 0.01% or less.
[0033] The chemical composition of the titanium alloy ingot is analyzed using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). The O content is measured using an inert gas fusion-thermal conductivity method. The Al content, Fe content, Sn content, Zr content, Mo content, Si content, Cu content, Nb content, V content, Y content, Cr content, Ni content, and Mn content of the titanium alloy ingot are measured in accordance with "JIS H 1632-2:2014 Titanium-ICP Atomic Emission Spectroscopic Analysis Method-Part 2: Palladium, Manganese, Iron, Magnesium, Silicon, Aluminum, Vanadium, Nickel, Chromium, Tin, Copper, Molybdenum, Zirconium, Niobium, Tantalum, Cobalt, and Yttrium Determination Method". The O content of the titanium alloy ingot is measured in accordance with "JIS H 1620:1995 Determination Method of Oxygen in Titanium and Titanium Alloys". The N content of titanium alloy ingots is measured in accordance with "JIS H 1612:1993 Determination of nitrogen in titanium and titanium alloys". The C content of titanium and titanium alloys is measured in accordance with "JIS H 1617:1995 Determination of carbon in titanium and titanium alloys". The H content of titanium alloy ingots is measured in accordance with "JIS H 1619:2012 Titanium and titanium alloys - Determination of hydrogen". The B content of titanium alloy ingots is measured in accordance with "JIS H 1632-3:2014 Titanium - ICP atomic emission spectrometry - Part 3: Determination of boron".
[0034] Next, the circumferential length L (mm) and cross-sectional area S (mm 2 ) relationship will be explained.
[0035] [Cross-sectional area S(mm 2 Ratio of the perimeter L (mm) of the cross section to the circumference L / S: 0.010 or more The α+β type titanium alloy ingot for hot working according to this embodiment has a cross-sectional area S (mm 2 The ratio L / S of the perimeter L (mm) of the cross section to the circumference L of the cross section is 0.010 or more.
[0036] In order to improve the surface quality of the bar, it is effective to make the cast structure of the titanium alloy ingot finer. When the volume of the titanium alloy ingot is large, it takes a long time to solidify, so the grain size of the cast structure becomes large. If the grain size is large, recrystallization is difficult to occur, and when the titanium alloy ingot is hot-rolled into a bar, the strain mismatch at the grain boundary during rolling becomes large, making it easier for cracks and voids to occur, and the surface is more likely to wrinkle during hot rolling, resulting in deep scratches.
[0037] If the surface area per volume of the titanium alloy ingot is large, the heat extraction is large, the time until solidification is shortened, and the structure can be made small. In the α+β type titanium alloy ingot for hot working according to this embodiment, the area S (mm 2 The degree of heat removal is evaluated using the ratio L / S of the perimeter L (mm) of the cross section to the circumference of the tube, and L / S should be 0.010 or more.
[0038] From the viewpoint of heat dissipation, the larger the L / S, the better, so there is no particular upper limit. For a normal shape, the L / S is 0.050 or less, or about 0.030 or less.
[0039] [The average crystal grain size D of the cast structure at a position 10 mm from the surface of the α+β type titanium alloy ingot toward the central axis of the α+β type titanium alloy ingot in the longitudinal direction of the α+β type titanium alloy ingot in a portion of 20 to 80% of the total length of the α+β type titanium alloy ingot in the longitudinal direction from one end face to the other end face of the two longitudinal ends of the α+β type titanium alloy ingot: D≦10 mm and D≦L / 100] In the hot working α+β titanium alloy ingot according to the present embodiment, the average crystal grain size D of the cast structure at a position 10 mm from the surface of the α+β titanium alloy ingot toward the central axis in the longitudinal direction is 10 mm or less in a portion of 20 to 80% of the total length of the α+β titanium alloy ingot from one end face of the two end faces in the longitudinal direction of the α+β titanium alloy ingot toward the other end face, and the average crystal grain size D and the circumferential length L of the cross section satisfy D≦L / 100. By making the structure of the hot working α+β titanium alloy ingot according to the present embodiment such a structure, when a compressive strain acts in the circumferential direction of the ingot during rolling, the strain at each grain boundary is relaxed, and the occurrence of cracks and voids is suppressed when the titanium alloy ingot is hot rolled into a bar. As a result, the formation of deep scratches on the surface of the bar can be suppressed. In the following, the portion from one of the two longitudinal end faces of the α+β type titanium alloy ingot to the other end, which corresponds to 20 to 80% of the total longitudinal length of the α+β type titanium alloy ingot, may be referred to as the longitudinal center portion.
[0040] The crystal grains constituting the cast structure are equiaxed and columnar, but at the position 10 mm from the surface in the center of the cross section of the hot working α+β type titanium alloy ingot according to this embodiment, most of them are columnar, and the variation of the cast structure in the longitudinal direction is small. On the other hand, in the cross section at both ends except the longitudinal center, coarse equiaxed crystals may be formed at the position 10 mm from the surface in the center of the cross section. When coarse equiaxed crystals are formed, the average crystal grain size D of the cast structure at the position 10 mm from the surface in the center of the cross section may not satisfy D≦10 mm and D≦L / 100. In such a non-steady state part, in addition to those caused by the cast structure, for example, a significant temperature drop may cause a decrease in ductility or toughness, causing surface defects, or surface defects may occur due to collision with rolling equipment. Therefore, in order to improve the surface quality and improve the yield, it is more effective to improve the surface quality of the center part. Therefore, the average crystal grain size D is measured in a cross section at the center of the longitudinal direction of the titanium alloy ingot.
[0041] The cross section for calculating the average grain size D is prepared by the following method. First, the titanium alloy ingot is cut in a direction perpendicular to the longitudinal direction at the center of the longitudinal direction of the titanium alloy ingot, and the cut surface obtained is polished with emery paper and buff polishing. Next, the polished cut surface is corroded using nitric acid hydrofluoric acid with a nitric acid concentration of 10 mass% and a hydrofluoric acid concentration of 5 mass%. The corroded cut surface is used as the cross section for calculating the average grain size D. In addition, in the manufacturing process of the titanium alloy ingot, the surface of the titanium alloy ingot may be removed by grinding (or cutting) by about 5 mm. However, the average grain size D calculated at a position 10 mm from the surface of the titanium alloy ingot before polishing toward the longitudinal central axis and the average grain size D calculated at a position 10 mm from the surface of the titanium alloy ingot after polishing by 5 mm toward the longitudinal central axis (a position 15 mm from the surface of the titanium alloy ingot before polishing toward the longitudinal central axis) are approximately the same value. Therefore, the average crystal grain size D may be calculated at a position 10 mm from the surface before polishing toward the central axis in the longitudinal direction, or the average crystal grain size D may be calculated at a position 10 mm from the surface after polishing toward the central axis in the longitudinal direction.
[0042] Here, a method for measuring the average crystal grain size D will be described with reference to Fig. 1. Fig. 1 is a diagram for explaining a method for measuring the average crystal grain size D of an α+β type titanium alloy ingot for hot working according to one embodiment of the present invention. Fig. 1 shows one of the semicircles obtained by dividing a titanium alloy ingot having a circular cross section along a straight line passing through the center of the cross section.
[0043] The average grain size D is calculated from the cross section of the central part of the titanium alloy ingot in the longitudinal direction. In detail, in the cross section of the central part of the titanium alloy ingot in the longitudinal direction, the number of grain boundaries that intersect with the line l that defines the shape of the cross section is calculated at a position 10 mm from the surface of the titanium alloy ingot toward the central axis in the longitudinal direction. In FIG. 1, the line l that defines the shape of the cross section is shown by a broken line. For example, in FIG. 1, the shape of the cross section A is circular, so the line l for calculating the number of grain boundaries is a line that defines a circle. The average grain size D is calculated by dividing the length of the line l by the number of grain boundaries.
[0044] [Thickness 80mm or more] The α+β type titanium alloy ingot for hot working according to this embodiment has a thickness of 80 mm or more.
[0045] Although the details will be described later, the α+β type titanium alloy ingot for hot working according to this embodiment is manufactured by irradiating the surface of molten titanium poured into a mold with an electron beam or plasma. In the technology described in the above-mentioned Patent Document 1, the surface of a solid titanium material such as a titanium briquette is irradiated with an electron beam or plasma. In the technology described in Patent Document 1, since the surface of a solid titanium material is irradiated with an electron beam or plasma, the melting depth is limited. If the output of the electron beam is increased in order to deepen the melting depth, the cooling rate after melting becomes slow and the crystal grains become coarse. On the other hand, if the electron beam or plasma is appropriately controlled and irradiated to the surface of the molten titanium, the generation of coarse crystal grains is suppressed. Therefore, by irradiating the surface of the molten titanium with an electron beam or plasma, it is possible to manufacture a larger-sized titanium alloy ingot that can suppress surface defects when hot-worked into a bar material without blooming forging. Therefore, the thickness of the α+β type titanium alloy ingot for hot working according to this embodiment is set to 80 mm or more. The thickness of the hot working α+β titanium alloy ingot according to this embodiment is preferably 130mm or more, more preferably 200mm or more.On the other hand, the upper limit of the thickness of the hot working α+β titanium alloy ingot according to this embodiment is not particularly limited, and for example, the thickness of the hot working α+β titanium alloy ingot according to this embodiment may be 400mm or less, or 350mm or less.
[0046] The thickness here refers to the length of the short side of the cross section when it is rectangular, and refers to the diameter of the cross section when it is circular. Also, when the cross section is a polygon with pentagons or more sides, it refers to the equivalent circle diameter of the cross section. The equivalent circle diameter here refers to the diameter of a circle equivalent to the area of the cross section. Polygonal cross sections also include cross sections in which at least one of the four corners of a quadrangle, such as a rectangle, is cut out. In this way, polygonal cross sections can have various shapes, but even in such cases, the diameter of the cross section refers to the equivalent circle diameter of the cross section. The width of the α+β type titanium alloy ingot for hot working according to this embodiment is determined by the size of the mold, and does not need to be specified. However, the lower limit may be equal to or greater than the thickness, and the upper limit may be 2m or less. The width here refers to the length of the long side of the cross section when the cross section is rectangular. Also, when the cross section is a polygon with pentagons or more sides, the width of the titanium alloy ingot is equal to the thickness.
[0047] In addition, since the hot working α+β titanium alloy ingot according to this embodiment is produced by casting, the lower and upper limits of length are not specified. Considering the equipment, the length of the hot working α+β titanium alloy ingot according to this embodiment can be 2m or more, and 7m or less.
[0048] So far, the hot working α+β type titanium alloy ingot according to this embodiment has been described. The bar material manufactured using the hot working α+β type titanium alloy ingot according to this embodiment can be used as a material for a molded object produced by a 3D printer.
[0049] Next, the preferred manufacturing method for obtaining the α+β type titanium alloy ingot for hot working according to the present embodiment will be described. The manufacturing method of the α+β type titanium alloy ingot described below is merely an example, and is not limited to the following manufacturing method.
[0050] The hot working α+β type titanium alloy ingot according to this embodiment is manufactured by electron beam melting or plasma melting using sponge titanium, mother alloy, titanium scrap, etc. as melting raw material. The electron beam melting and plasma melting are also called cold hearth melting because they use a cold hearth.
[0051] The electron beam melting method and the plasma melting method are methods for producing ingots by injecting molten raw materials into a cold hearth using electron beam or plasma irradiation, or by melting the raw materials on the cold hearth, and then pouring the melted raw materials into a mold and pulling out the solidified ingot from the bottom of the mold.
[0052] In the cold hearth melting method, the molten pool in the mold where the raw material is melted is shallow, which has the advantage of making the grain size of the cast structure small, and the mold size has a large degree of freedom. Therefore, the manufacturing method of the hot working α+β type titanium alloy ingot according to this embodiment uses the cold hearth melting method.
[0053] The solidification structure of a titanium alloy ingot is affected by the heat transfer from the titanium alloy ingot to the side wall of the mold, the heat input to the molten metal surface by the electron beam or plasma, and the temperature of the molten metal poured into the mold, etc. By appropriately controlling these, the solidification structure can be controlled.
[0054] In the manufacturing method of the α+β type titanium alloy ingot for hot working according to the present embodiment, the pouring temperature when pouring the molten titanium alloy into the mold is the melting point of the titanium alloy + 200 ° C or less, the pouring speed when pouring the molten titanium alloy into the mold is 0.05 ton / h or more and 2.00 ton / h or less, and the average irradiation density of the electron beam or plasma within 20 mm from the mold surface is 50 to 80% of the average irradiation density of the electron beam or plasma inside 20 mm from the mold surface. By controlling the pouring temperature, pouring speed and average irradiation density as described above, the molten metal temperature in the mold can be lowered, and the grain size of the titanium alloy ingot can be suppressed from becoming coarse. Here, the ratio of the average irradiation density of the electron beam or plasma within 20 mm from the mold surface to the average irradiation density of the electron beam or plasma inside 20 mm from the mold surface is the irradiation ratio.
[0055] Here, a method for controlling the irradiation ratio of the electron beam or plasma will be described with reference to Fig. 2 and Fig. 3. Fig. 2 is a diagram for explaining a first method for controlling the irradiation ratio of the electron beam or plasma. Fig. 3 is a diagram for explaining a second method for controlling the irradiation ratio of the electron beam or plasma. Figs. 2 and 3 show a schematic diagram of the molten metal inside the mold as viewed from the irradiation direction of the electron beam or plasma. Region 2 shown in Figs. 2 and 3 shows the molten metal within 20 mm from the interface 1 where the molten metal and the inner surface of the mold come into contact, and region 3 shows the molten metal within 20 mm from the mold surface.
[0056] Solidification occurs mainly by heat transfer to the side walls of the mold. The surface of the molten metal in the mold is heated by electron beam or plasma to prevent solidification due to heat transfer. As shown in Figure 2, the irradiation area B of the electron beam or plasma is narrower than the mold area, so the entire surface of the molten metal is heated by scanning the electron beam or plasma as shown by the solid arrow in Figure 2.
[0057] The number of electron beams or plasma irradiated to the molten metal may be one or more. Below, a method for controlling the irradiation ratio in each of the cases where there is one electron beam or plasma and the case where there are two electron beams or plasma will be described.
[0058] First, a first control method will be described, which is a method for controlling the irradiation ratio when a single electron beam or plasma is irradiated to the molten metal. When a single electron beam or plasma is irradiated to the molten metal, the scanning speed of the electron beam or plasma irradiated to the molten metal located within 20 mm from the inner surface of the mold is set to 1.25 to 2.00 times the scanning speed of the electron beam or plasma irradiated to the molten metal located 20 mm inside from the mold surface. This makes it possible to set the irradiation ratio of the electron beam or plasma to 50 to 80%.
[0059] Next, a second control method, which is a method for controlling the irradiation ratio when two electron beams or plasmas are irradiated to the molten metal, will be described. When two electron beams or plasmas are irradiated to the molten metal, one electron beam or plasma is scanned over the entire molten metal surface, and the other electron beam or plasma is scanned over the surface of the molten metal located 20 mm inside from the mold surface. In FIG. 3, the solid arrow indicates the scanning path of the electron beam or plasma scanned over the entire molten metal surface, and the dashed arrow indicates the scanning path of the electron beam or plasma scanned over the surface of the molten metal located 20 mm inside from the mold surface. The number of scans of each of the two electron beams or plasmas is changed according to the irradiation ratio. For example, when the irradiation ratio is 80%, the electron beam or plasma scanned over the entire molten metal surface is scanned 80 cycles, and the electron beam or plasma scanned over the surface of the molten metal located 20 mm inside from the mold surface is scanned 20 cycles. Here, one cycle refers to scanning the electron beam or plasma over the entire desired range. The scanning speeds of the two electron beams or plasmas may be equal to each other. The outputs of the two electron beams or plasmas may be equal to each other. This allows the irradiation ratio of the electron beam or plasma to be 50 to 80%.
[0060] By controlling the solidification conditions of the titanium alloy having the above-mentioned components to obtain a titanium alloy ingot, it is possible to control the formation of the grain boundary α phase in the titanium alloy ingot and reduce the depth of surface defects in the bar material obtained by rolling the titanium alloy ingot.
[0061] As described above, according to the present invention, a bar having good surface properties can be produced by directly hot rolling an ingot of an α+β titanium alloy containing Al, Fe, and O without blooming forging. In addition, when producing a bar using the α+β titanium alloy ingot for hot working according to this embodiment, blooming forging can be omitted, so that the bar can be produced industrially at low cost. Furthermore, as will be described below, according to the α+β titanium alloy ingot for hot working according to this embodiment, the surface defects of the bar are suppressed, so that the bar can be stably produced.
[0062] The effect of the present invention can be confirmed by the depth of surface defects of a titanium alloy bar obtained by rolling a titanium alloy ingot. The depth of surface defects is evaluated by the following method.
[0063] The bar is cut perpendicular to the axial direction, and the cut surface is polished to a mirror finish. Then, the depth of the surface flaw is measured using an optical microscope at a magnification of 15 times. The flaw depth ratio (%) = (maximum surface flaw depth) / (circular equivalent diameter of the bar) x 100 is calculated from the depth of the surface flaw with the maximum surface flaw depth within the observed field of view and the circular equivalent diameter of the bar, and this is used as an index of the surface quality. The flaw depth is examined at five locations in the center of the bar in the longitudinal direction where flaws are visually confirmed on the bar surface. In detail, a cross section perpendicular to the axial direction of the bar is obtained at each of the five locations in the center of the bar in the longitudinal direction where flaws are visually confirmed on the bar surface. The five cross sections are observed using an optical microscope at a magnification of 15 times, and the arithmetic average value of the maximum depths obtained at each cross section is taken as the maximum surface flaw depth in the above formula. If there are less than five locations where defects are visually confirmed in the center of the longitudinal bar, the maximum surface defect depth is calculated based on the locations where defects are visually confirmed. If there are six or more locations where defects are visually confirmed in the center of the longitudinal bar, the five locations starting from the largest defect are measured. If the defects do not fit in one field of view, the field of view may be moved to calculate the defect depth. As described above, in non-steady-state areas such as both ends of the longitudinal bar except for the center, surface defects may occur due to, for example, a significant temperature drop that reduces ductility and toughness, or surface defects may occur due to collision with rolling equipment, in addition to those caused by the cast structure. In order to exclude the influence of such surface defects and evaluate the occurrence of surface defects caused by the size of crystal grains, the maximum surface defect depth calculated from the depth of defects confirmed in the center of the longitudinal bar is used to calculate the defect depth ratio, which is an index of surface properties. Here, the central portion of the rod in the longitudinal direction refers to a portion extending from one of the two longitudinal end faces of the α+β type titanium alloy rod to the other end, which is 20 to 80% of the entire longitudinal length of the α+β type titanium alloy rod.
[0064] The results of confirming the effect of the present invention based on the depth of surface defects will be described in the following examples. Note that the examples shown below are merely examples of the present invention, and the present invention is not limited to the following examples. EXAMPLES
[0065] [Example 1] (Manufacturing titanium alloy ingots and bars) Titanium alloy ingots were manufactured by electron beam melting (EBM) for No. 1 to No. 29 shown in Table 1. The temperature of the molten titanium alloy poured from the hearth into the molds of the shapes shown in Table 1 was set to melting point + 200°C or lower (only No. 1 was above melting point + 200°C), the pouring speed was set to 0.05 to 2.0 ton / h, and the average irradiation density of the electron beam from 20 mm from the mold surface to the center was set to 0.05 to 0.10 kW / cm. 2 The average irradiation density of the electron beam within 20 mm from the mold surface was set to 50-100% of the average irradiation density of the electron beam from 20 mm to the center side from the mold surface, that is, the irradiation ratio was set to 50-100%, and a titanium alloy ingot having the chemical composition shown in Table 2 and the cross-sectional circumference L, cross-sectional area S, and average crystal grain size D shown in Tables 3A and 3B was manufactured. In Table 1, the average irradiation density of the electron beam from 20 mm to the center side from the mold surface is described as the "average irradiation density of the center", and the average irradiation density of the electron beam within 20 mm from the mold surface is described as the "average irradiation density of the surface side". With the output of the electron beam gun kept constant, the average irradiation density was controlled by changing the scanning speed of the electron beam irradiated to the molten metal located 20 mm inside from the mold surface and the scanning speed of the electron beam irradiated to the molten metal located within 20 mm from the inner surface of the mold.
[0066] Thereafter, the titanium alloy ingot was heated to 1200°C and rolled to φ100mm with an area reduction of 41-94%. For titanium alloy ingots No. 1-21, in which the cross section (mold shape) perpendicular to the casting direction of the titanium alloy ingot was 310mm x 440mm, a total of 17 passes of reverse rolling were performed until the cross section was 180mm x 195mm. The area reduction of the titanium alloy ingot after 17 passes of reverse rolling was 74%. After 17 passes of reverse rolling, 8 passes of caliber rolling were performed until the titanium alloy ingot was φ100mm, and the area reduction was 94% compared to the titanium alloy ingot before reverse rolling, to obtain a bar material. For titanium alloy ingots No. 22 to No. 28, whose mold shape was φ200 mm to φ500 mm, reverse rolling and groove rolling were performed in the same manner as above, and for titanium alloy ingot No. 29, whose mold shape was φ130 mm, only the groove rolling was performed as described above.
[0067] In addition, Nos. 30 and 31 shown in Table 1 are reference examples in which a titanium alloy ingot was manufactured according to the conventional technology, and then blooming forging and hot rolling were performed to manufacture a bar material. In the example of No. 30, a titanium alloy ingot of φ750 mm was manufactured by consumable electrode vacuum arc melting (VAR), and the titanium alloy ingot was blooming forged to manufacture a billet of 310 × 440 mm. In the example of No. 31, a titanium alloy ingot was manufactured by the same method as No. 30, and a round bar of φ300 mm was manufactured by blooming forging. Then, both Nos. 30 and 31 were heated to 1200 ° C and rolled to φ100 mm, similar to Nos. 1 to 29. In addition, since the titanium alloy ingots of Nos. 30 and 31 were manufactured by VAR, the center average irradiation density, the surface average irradiation density, and the irradiation ratio of Nos. 30 and 31 in Table 1 are not listed.
[0068] [Table 1]
[0069] (Chemical composition of titanium alloy ingot) The Al content, Fe content, Mo content, and Nb content of each titanium alloy ingot were measured in accordance with "JIS H 1632-2:2014 Titanium-ICP Atomic Emission Spectroscopic Analysis Method-Part 2: Palladium, Manganese, Iron, Magnesium, Silicon, Aluminum, Vanadium, Nickel, Chromium, Tin, Copper, Molybdenum, Zirconium, Niobium, Tantalum, Cobalt, and Yttrium Determination Method". The O content of the titanium alloy ingot was measured in accordance with "JIS H 1620:1995 Determination of Oxygen in Titanium and Titanium Alloys". In Example 1, there are no elements other than Al, Fe, and O whose contents in the titanium alloy ingot are intentionally controlled, so all elements other than Ti and the elements shown in Table 2 are considered to be impurities. In addition, the Mo content and Nb content were within the range considered to be impurities, so their respective contents were considered to be 0%. Table 2 shows the chemical composition of titanium alloy ingots, and whether or not they satisfy the formula (1): 0.02%≦[O]≦([Al]-[Fe]-0.5×[Mo]-0.5×[Nb]+1.0) / 100. In the "Pass or Fail of Formula (1)" column in Table 2, cases where formula (1) is satisfied are marked as "Good," and cases where it is not satisfied are marked as "Bad."
[0070] [Table 2]
[0071] (Cross-sectional perimeter L and cross-sectional area S) The shrinkage during solidification of each produced titanium alloy ingot has almost no effect on the evaluation of the ratio L / S of the cross-sectional perimeter L to the cross-sectional area S. Therefore, the cross-sectional area S and the cross-sectional perimeter L of each titanium alloy ingot were calculated from the cross-sectional shape of the mold.
[0072] (Measurement of average crystal grain size D) The average crystal grain size D was measured by the following method. First, the ingot was cut in a direction perpendicular to the longitudinal direction at a position 50% of the total length of the ingot in the longitudinal direction from one end face to the other end face of the two longitudinal ends of the ingot, and the cut surface obtained was polished with emery paper and buff polishing. Next, the polished cut surface was corroded using nitric acid hydrofluoric acid with a nitric acid concentration of 10 mass% and a hydrofluoric acid concentration of 5 mass%. The number of grain boundaries was measured at a position 5 mm from the short side toward the center of the corroded cut surface.
[0073] In the item "D≦L / 100" in Tables 3A and 3B, those in which the average crystal grain size D satisfies D≦L / 100 are indicated as "Good," and those in which the average crystal grain size D does not satisfy D≦L / 100 are indicated as "Bad."
[0074] (Surface properties of bar material) The obtained bar was cut perpendicular to the axial direction of the bar at each of the five locations where defects were visually observed on the bar surface, and the cut surfaces were polished to a mirror finish, and the depth of the surface defects was measured using an optical microscope. In detail, a cross section perpendicular to the axial direction of the bar was obtained at each of the five locations where defects were visually observed on the bar surface in the center of the longitudinal direction. The five cross sections were observed with an optical microscope at a magnification of 15 times, and the average value of the maximum depth obtained at each cross section was taken as the maximum surface defect depth in the following formula. If there were fewer than five locations where defects were visually observed in the center of the longitudinal direction of the bar, the maximum surface defect depth was calculated based on the locations where defects were visually observed. If there were six or more locations where defects were visually observed in the center of the longitudinal direction of the bar, the five locations starting from the largest defects were measured. When the flaw did not fit within one field of view, the field of view was shifted and the flaw depth was calculated.
[0075] The flaw depth ratio (%) = (maximum surface flaw depth) / (circular equivalent diameter of the bar) x 100 was calculated from the maximum surface flaw depth within the observed field of view and the circular equivalent diameter of the bar, and the surface quality was judged to be good when the flaw depth ratio was 3.0% or less, and bad when the flaw depth ratio was more than 3.0%. The results are shown in Tables 3A and 3B.
[0076] [Table 3A]
[0077] [Table 3B]
[0078] It was confirmed that the α+β type titanium alloy ingots of the present invention had surface properties equivalent to those of the conventional examples (No. 30 and No. 31) even when they were hot rolled without blooming forging.
[0079] In addition, it is easy to distinguish between the as-cast structure of the α+β type titanium alloy ingot of the present invention and the forged structure of Nos. 30 and 31 by observing the structure.
[0080] Nos. 1, 5, 6, 11, 13, 14, 15, 17, 19 to 23, 26, 28, and 29 are comparative examples.
[0081] In No. 1, the pouring temperature exceeded the melting point plus 200°C, the irradiation ratio was high at 100%, and the relationship between the average crystal grain size D and the circumference L of the cross section, D≦L / 100, was not satisfied. As a result, the average crystal grain size D was outside the range of the present invention, and the surface properties after rolling were poor.
[0082] Nos. 5, 6, 11, 17, and 19 did not satisfy formula (1), and as a result, the surface properties after rolling were poor. In Nos. 15 and 26, the irradiation ratio was outside the preferred range, and the grain size was outside the range of the present invention, resulting in poor surface properties after rolling. In No. 22, the irradiation ratio was outside the preferred range, the ratio L / S of the perimeter L of the cross section to the area S of the cross section was outside the range of the present invention, and the grain size was outside the range of the present invention, resulting in poor surface properties after rolling. No. 29 did not satisfy the relationship D≦L / 100 between the average crystal grain size D and the circumferential length L of the cross section, and therefore had poor surface properties after rolling. In No. 13, the titanium alloy ingot had a high Fe content, and as a result, the surface quality after rolling was poor. In No. 14, the titanium alloy ingot had a high Al content, and as a result, the surface quality after rolling was poor. In No. 20, the Fe content of the titanium alloy ingot was low, and the surface quality after rolling was poor. In No. 21, the Al content of the titanium alloy ingot was low, and the surface quality after rolling was poor. In No. 23, the ratio L / S of the perimeter L of the cross section to the area S of the cross section was less than 0.010, and the surface quality after rolling was poor. No. 28 did not satisfy the relationship D≦L / 100 between the average crystal grain size D and the circumferential length L of the cross section. Therefore, when compressive strain acts in the circumferential direction of the ingot during rolling, the strain at each crystal grain boundary is not relaxed, resulting in the generation of voids and poor surface properties after rolling.
[0083] [Example 2] (Manufacturing titanium alloy ingots and bars) Using a mold with a cross section perpendicular to the casting direction of 310 mm x 440 mm, the pouring temperature was set to melting point + 200°C or less, the pouring rate was 0.5 ton / h, and the average irradiation density of the electron beam from 20 mm from the mold surface to the center was 0.10 kW / cm 2 The electron beam irradiation density within 20 mm from the mold surface was set to 50-80% of the central area, i.e., the irradiation ratio was 70%, to produce titanium alloy ingots having the chemical composition and average crystal grain size D shown in Table 4. The length of the produced titanium alloy ingot was 4200 mm. Thereafter, similarly to Example 1, each titanium alloy ingot was heated to 1200°C, and then rolled to φ100 mm at a reduction in area of 94% by reverse rolling and groove rolling to obtain a bar.
[0084] (Chemical composition of titanium alloy ingot) The chemical composition of the titanium alloy ingot was measured by the following method. The Al content, Fe content, Mo content, and Nb content of each titanium alloy ingot were measured in the same manner as in Example 1. The O content of the titanium alloy ingot was measured in accordance with "JIS H 1620:1995 Method for determining oxygen in titanium and titanium alloys". The Si content, Zr content, Sn content, and Cu content were measured in accordance with "JIS H 1632-2:2014 Titanium-ICP atomic emission spectroscopic analysis method-Part 2: Method for determining palladium, manganese, iron, magnesium, silicon, aluminum, vanadium, nickel, chromium, tin, copper, molybdenum, zirconium, niobium, tantalum, cobalt, and yttrium". Table 4 shows the chemical composition of titanium alloy ingots, and whether or not it satisfies formula (1): 0.02%≦[O]≦([Al]-[Fe]-0.5×[Mo]-0.5×[Nb]+1.0) / 100. In the "Pass or Fail of Formula (1)" section of Table 4, cases where formula (1) is satisfied are marked as "Good," and cases where it is not satisfied are marked as "Bad." Additionally, "-" in Table 4 indicates that no intentional addition was made.
[0085] [Table 4]
[0086] (Measurement of average crystal grain size D) The average crystal grain size D was measured in the same manner as in Example 1. In the "D≦L / 100" section of Table 5, the average crystal grain size D that satisfied D≦L / 100 was indicated as "Good," and the average crystal grain size D that did not satisfy D≦L / 100 was indicated as "Bad."
[0087] (Surface properties of bar material) The obtained rods were cut perpendicular to the axial direction of the rod at five locations where scratches were visually observed on the surface of the rod, and the cut surfaces were polished to a mirror finish.The depth of the surface scratches was then measured using an optical microscope.
[0088] The flaw depth ratio (%) = (maximum surface flaw depth) / (circular equivalent diameter of bar) × 100 was calculated from the maximum surface flaw depth within the observed field of view and the circular equivalent diameter of the bar, and a flaw depth ratio of 3.0% or less was determined to have good surface quality, and a flaw depth ratio of more than 3.0% was determined to have bad surface quality. The results are shown in Table 5.
[0089] [Table 5]
[0090] It was confirmed that the α+β type titanium alloy ingots of the present invention can obtain good surface properties even when hot rolling is performed without blooming forging. Nos. 2, 3, 6, 8, and 13 do not satisfy formula (1) and have poor surface properties.
[0091] Although the preferred embodiment of the present invention has been described in detail above, the present invention is not limited to such an example. It is clear that a person having ordinary knowledge in the technical field to which the present invention pertains can conceive of various modified or altered examples within the scope of the technical ideas described in the claims, and it is understood that these also naturally fall within the technical scope of the present invention.
Claims
1. An alpha + beta titanium alloy ingot, In mass percent, Al: 2.5-8.0%, Fe: 0.5-3.0%, Sn: 0-3.0%, Zr: 0 to 3.0%, Mo: 0-3.0%, Si: 0-3.00%, Cu: 0-3.0%, Nb: 0 to 3.0%, and It has a chemical composition containing an amount of O satisfying the following formula (1), with the balance being Ti and impurities, The area S (mm 2 The ratio L / S of the perimeter L (mm) of the cross section to the perimeter L (mm) is 0.010 or more, In the cross section of the α+β titanium alloy ingot, which is 20 to 80% of the total length of the α+β titanium alloy ingot in the longitudinal direction from one of the two end faces in the longitudinal direction to the other end face, the average crystal grain size D of the cast structure calculated on a line corresponding to the shape of the cross section at a position 10 mm toward the inside of the α+β titanium alloy ingot from the surface of the α+β titanium alloy ingot satisfies D≦10 mm and D≦L / 100; The α+β type titanium alloy ingot is characterized in that the thickness of the α+β type titanium alloy ingot is 80 mm or more. 0.02%≦[O]≦([Al]−[Fe]−0.5×[Mo]−0.5×[Nb]+1.0) / 100 (1) Here, [X] indicates the content of element X in units of mass %.
2. The α+β type titanium alloy ingot according to claim 1, further comprising at least one of Sn, Zr, Mo, Cu, and Nb in an amount of 3.0% or less each in place of a portion of the Ti.
3. A method for manufacturing a rod, comprising hot rolling an α+β type titanium alloy ingot as described in claim 1 or 2.
Citation Information
Patent Citations
Manufacture of titanium and titanium alloy ingot
JP1991285028A
Titanium alloy incorporated with boron added
JP2004277873A
Titanium hot rolling ingot being hard to cause surface flaw and its manufacturing method
JP2016128172A
Metal powder for laminate molding and laminate molded body using metal powder
JP2017222899A
Titanium material for hot rolling
JP2019115933A